The Transformation of Batak Toba Wedding Ceremonies: Navigating Tradition and Modernity - Silaban, Jelly; Sembiring, Pemina; Perangin-angin, Alemina Br (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
The Batak Toba traditional wedding ceremony is a significant cultural practice that reflects the social identity and kinship structure of the Batak Toba community. This study aims to analyze the transformation of Batak Toba wedding rituals in the modern context, particularly in Medan City, where urbanization, modernization, and globalization strongly influence traditional practices. Using Alexander Duranti's theoretical framework, this research explores the ideological, symbolic, and structural changes in key stages of the ceremony, such as marhusip, marhata sinamot, and ulaon pesta. A qualitative methodology was employed, incorporating in-depth interviews, participant observations, and document analysis. The findings reveal that while core elements such as the exchange of ulos and the reinforcement of kinship ties remain intact, significant shifts have occurred, including a transition from communal preparations to catering services and the simplification of rituals due to economic pressures and modern lifestyles. This study lies in its specific focus on the Batak Toba community in an urban setting, highlighting how traditional ceremonies adapt to modern influences while retaining their cultural essence.